The Role of the Cytoskeleton and Myosin-Vc in the Targeting of KCa3.1 to the Basolateral Membrane of Polarized Epithelial Cells - Farquhar, Rachel E.; Rodrigues, Ely; Hamilton, Kirk L. (Frontiers in Physiology, 2017)
Understanding the targeting of KCa3.1 to the basolateral membrane (BLM) of polarized epithelial cells is still emerging. Here, we examined the role of the cytoskeleton (microtubules and microfilaments) and Myosin-Vc (Myo-Vc) in the targeting of KCa3.1 in Fischer rat thyroid epithelial cells. We used a pharmacological approach with immunoblot (for the BLM expression of KCa3.1), Ussing chamber (functional BLM expression of KCa3.1) and siRNA experiments. The actin cytoskeleton inhibitors cytochalasin D (10 µM, 5 hr) and latrunculin A (10 µM, 5 hr) reduced the targeting of KCa3.1 to the BLM by 88±4% and 70±5%, respectively. Colchicine (10 µM, 5 hr) a microtubule inhibitor reduced targeting of KCa3.1 to the BLM by 63±7% and decreased 1-EBIO-stimulated KCa3.1 K+ current by 46±18%, compared with control cells. ML9 (10 µM, 5 hr), an inhibitor of myosin light chain kinase, decreased targeting of the channel by 83±2% and reduced K+ current by 54±8% compared to control cells. Inhibiting Myo-V with 2,3-butanedione monoxime (10 mM, 5 hr) reduced targeting of the channel to the BLM by 58±5% and decreased the stimulated current of KCa3.1 by 48±12% compared with control cells. Finally, using siRNA for Myo-Vc, we demonstrated that knockdown of Myo-Vc reduced the BLM expression of KCa3.1 by 44±7% and KCa3.1 K+ current by 1.04±0.14 μA compared with control cells. These data suggest that the microtubule and microfilament cytoskeleton and Myo-Vc are critical for the targeting of KCa3.1.